2013
DOI: 10.1590/s1517-83822013000200034
|View full text |Cite
|
Sign up to set email alerts
|

Semi-scale production of PHAs from waste frying oil by Pseudomonas fluorescens S48

Abstract: The present study aimed at developing a strategy to improve the volumetric production of PHAs by Pseudomonas fluorescens S48 using waste frying oil (WFO) as the sole carbon source. For this purpose, several cultivations were set up to steadily improve nutrients supply to attain high cell density and high biopolymer productivity. The production of PHAs was examined in a 14 L bioreactor as one-stage batch, two-stage batch, and high-cell-density fed-batch cultures. The highest value of polymer content in one-stag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 24 publications
1
29
0
Order By: Relevance
“…Sample bioplastic film was prepared by dissolving 50 mg PHB extract in 10 ml chloroform according to Rawia et al [15]. …”
Section: Methodsmentioning
confidence: 99%
“…Sample bioplastic film was prepared by dissolving 50 mg PHB extract in 10 ml chloroform according to Rawia et al [15]. …”
Section: Methodsmentioning
confidence: 99%
“…In a study, palladium (Pd) NPs were introduced into different polymer matrix and thermal degradation of these polymers were investigated. This study concluded that thermal degradation of polystyrene (PS), PP, and methyl methacrylate were decreased by Pd NPs, while thermal degradation of polyamide (PA) and poly(ethylene‐terephthalate) (PET) were enhanced. In another study the effect of silver sulfide on thermal degradation of PHB was studied and this study concluded that PHB is degraded at lower temperature in the presence of silver sulfide .…”
Section: Need For Chemical Modifications Of Phasmentioning
confidence: 99%
“…Polyhydroxyalkanoates are one of the biodegradable and biocompatible thermoplastics . These are larger molecules that are produced by Gram‐negative and Gram‐positive bacteria .…”
Section: Introductionmentioning
confidence: 99%
“…After incubation, the cells were harvested by centrifugation at 6000 rpm for 10 minutes and treated with sodium hypochlorite for 60 minutes. The cells were then successively treated with 5 ml acetone, methanol, and boiling chloroform with intermittent centrifugation . The treated cells were filtered and the filtrate was collected in a Makarthy tube.…”
Section: Methodsmentioning
confidence: 99%